Political crime and denunciation in the 1950s cases for making communist propaganda - Gülen, Seval. (Thesis (M.A.) - Bogazici University. Atatürk Institute for Modern Turkish History, 2010., 2010)
This thesis is based on the relationship between political crime and denunciation in the 1950s in Turkey. It analyzes the issue of whether there was an atmosphere of ordinary people denouncing each other in that era or not. The paper examines Republican authorities' view of the 'other'- the communists. I have tried to make a detailed analysis of cases- reasons of notice, relationship status of denouncer, authorities' approach to cases or legal results- so as to interpret that our beliefs on the approach of Republican authorities to the communists or any other groups is how authentic in daily life of ordinary people. The cases provided me to see the threats of political system in the eyes of ordinary people and the issues they need to denounce a person as insulting this system. In this respect, I use the case files with political crimes in the 1950s which are tried by Istanbul 1st High Penal Court in Sultanahmet Courthouse. In my thesis study, I make a detailed analysis of these case files, especially ethnic and religious identity of the accused, relationship status of the denouncer and his/her reason for denouncing, defense of the accused, perspective of the members of the court, and final decision of the court. Such a comprehensive analysis of those case files provide for me to understand, in first phase, social and political climate of the 1950s of Turkey and secondly, the experience of this climate among ordinary people of the society.
Keywords: Denunciation (Criminal law) -- Turkey.; Political crimes and offenses -- Turkey.